2020
DOI: 10.17476/jmbs.2020.9.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Efficacy and Diabetes Remission Predictors Following ‘Sleeve Gastrectomy with Loop Duodenojejunal Bypass’ Surgery

Abstract: Purpose Laparoscopic sleeve gastrectomy with loop duodenojejunal bypass (SLDJB) is a novel metabolic surgery that is a modification of the single anastomosis duodenoileal bypass with sleeve. Compared to conventional surgeries, SLDJB is highly effective in inducing diabetes remission. This study analyzed the metabolic efficacy of SLDJB. Materials and Methods Seventy-eight patients with obesity and diabetes who underwent SLDJB between May 2013 and October 2017 were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, some previous studies have reported a decline in serum albumin levels after SASI bypass; however, we found no cases of hypoalbuminemia or hypoglycemia. Some studies have indicated a reversal of SASI to SG due to hypoalbuminemia or excessive weight loss > 100% [3, 11, 18, 25]. In the present study, 8 /116 patients had excessive weight loss (EWL% > 100%), which were revised to SG, mostly in the second year after the surgery.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed, some previous studies have reported a decline in serum albumin levels after SASI bypass; however, we found no cases of hypoalbuminemia or hypoglycemia. Some studies have indicated a reversal of SASI to SG due to hypoalbuminemia or excessive weight loss > 100% [3, 11, 18, 25]. In the present study, 8 /116 patients had excessive weight loss (EWL% > 100%), which were revised to SG, mostly in the second year after the surgery.…”
Section: Discussionmentioning
confidence: 50%